Information technology of creation forecasting models of non-linear time series in the conditions of heteroscedasticity - Шамша, Борис Владимирович; Гуд, Анастасия Юрьевна; Одейчук, Андрей Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents a problem of developing a procedure for pre-processing information in heteroscedasticity. It is proposed to use the statistics of recursive residuals to improve the capacity of standard tests to check ARCH processes.